2023
DOI: 10.1021/acsaem.2c03137
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Analogue-Assisted Formation of Iron–Nickel Selenide Porous Nanosheets for Enhanced Oxygen Evolution

Abstract: The development of active and stable electrocatalysts made from earth-abundant elements to accelerate the oxygen evolution reaction (OER) kinetics is of great significance for improving the efficiency of overall water splitting. Herein, a Prussian blue analogue (PBA)-assisted strategy to synthesize FeSe−NiSe nanosheets is reported. With this approach, porous FeSe−NiSe nanosheets supported on conductive Ni foam (NF) are fabricated via controlled chemical etching of Ni(OH) 2 /NF with Fe(CN) 6 3− and subsequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Similarly, in Figure e, the XPS spectrum of Fe 2p was dominated by Fe 3+ with peaks shifting to higher binding energies at 712.35 and 725.15 eV. The observed shifts in the Ni 2p and Fe 2p peaks toward higher binding energies suggest the formation of Ni/Fe metal oxyhydroxides . The XPS spectrum of Se demonstrated the same change trend as that after the oxygen evolution reaction.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Similarly, in Figure e, the XPS spectrum of Fe 2p was dominated by Fe 3+ with peaks shifting to higher binding energies at 712.35 and 725.15 eV. The observed shifts in the Ni 2p and Fe 2p peaks toward higher binding energies suggest the formation of Ni/Fe metal oxyhydroxides . The XPS spectrum of Se demonstrated the same change trend as that after the oxygen evolution reaction.…”
Section: Resultssupporting
confidence: 54%
“…The observed shifts in the Ni 2p and Fe 2p peaks toward higher binding energies suggest the formation of Ni/Fe metal oxyhydroxides. 45 The XPS spectrum of Se demonstrated the same change trend as that after the oxygen evolution reaction. As depicted in Figure 6f, the SeO x peak intensity increased and Se 3d peak decreased.…”
Section: Resultsmentioning
confidence: 61%
“…The catalyst not only demonstrates effectiveness and stability, but also exceeds established benchmarks, encompassing both nickel-based and precious-metal-based electrocatalysts. 9,23,29–33 Our findings shed light on the fundamental mechanisms responsible for the exceptional electrocatalytic performance of this Cu 2 NiBiSe 4 electrocatalyst. These insights offer a valuable direction for the methodical development of electrocatalysts that utilize nickel and other abundant elements.…”
Section: Introductionmentioning
confidence: 80%
“…The high-resolution Fe 2p XPS spectrum showed the Fe–Se bond at 706.2 eV, Fe 2p 3/2 at 710.1 eV, and Fe 2p 1/2 at 724.2 eV (Figure b) . The Se 3d spectrum displayed the Se 3d 5/2 peak at 53.7 eV and Se 3d 3/2 at 54.6 eV (Figure c) . The SeO x peak at 58.4 eV was originated from the surface oxidation of selenide .…”
mentioning
confidence: 98%
“…28 The Se 3d spectrum displayed the Se 3d 5/2 peak at 53.7 eV and Se 3d 3/2 at 54.6 eV (Figure 2c). 29 The SeO x peak at 58.4 eV was originated from the surface oxidation of selenide. 30 N 2 adsorption−desorption isotherms revealed that the Brunauer−Emmett−Teller (BET) specific surface area of HD-FeSe 2 is 79.8 m 2 g −1 , which is much larger than the FeSe 2 precursor (Figure S1a).…”
mentioning
confidence: 99%